2020
DOI: 10.1080/14789949.2020.1807585
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the characteristics associated with intimate partner stalking: a mixed methods structured review and narrative synthesis

Abstract: and a Registered forensic psychologist in the United Kingdom. Her research and practice focuses on the areas of self-harm, suicide and violence in forensic populations, the impact on prison staff of working in difficult environments, mental health services for offenders and organisational approaches to suicide and violence prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…The economic toll of stalking (e.g., medical care, mental health services, lost salary) has been estimated between US$235 and US$449 million for women in America ( Max et al, 2004 ). In forensic practice, stalking is often conceptualized as a continuation and extension of intimate partner violence (IPV); perpetrators of stalking and perpetrators of IPV do actually share a number of characteristics (e.g., substance misuse, history of IPV, prior criminal history, unemployment), although they also appear to show some key differences (e.g., greater variety of methods or patterns of pursuit behaviors among stalking perpetrators; Flowers et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The economic toll of stalking (e.g., medical care, mental health services, lost salary) has been estimated between US$235 and US$449 million for women in America ( Max et al, 2004 ). In forensic practice, stalking is often conceptualized as a continuation and extension of intimate partner violence (IPV); perpetrators of stalking and perpetrators of IPV do actually share a number of characteristics (e.g., substance misuse, history of IPV, prior criminal history, unemployment), although they also appear to show some key differences (e.g., greater variety of methods or patterns of pursuit behaviors among stalking perpetrators; Flowers et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…We also examined the relative importance of individual maladaptive personality facets in the statistical prediction of stalking behaviours. Based on the aforementioned literature on interpersonal aggression and pathological personality domains and facets, and considering the documented similarities between perpetrators of stalking and other forms of interpersonal violence such as IPV (Flowers et al, 2020), the following results were expected: (a) Level of personality impairment and pathological personality domains should be significantly correlated with stalking perpetration; (b) a gradient of frequency/severity of stalking behaviours should be observed across incremental severity degrees of personality pathology; (c) key individual statistical predictors of stalking perpetration should include facets from multiple pathological domains, most probably Antagonism, Disinhibition, and Negative Affectivity. Callousness, Risk Taking, and Hostility are likely to be among the most important facet predictors.…”
Section: The Present Studymentioning
confidence: 99%
“…They present diverse characteristics and clinical features (Mullen et al, 2009; Nijdam‐Jones et al, 2018). Furthermore, multiple studies have found personality pathology as a significant correlate of pursuit behaviours (Flowers et al, 2020). Most generally, previous studies have focused on the links between stalking perpetration and categorical personality disorder (PD) diagnoses from the Diagnostic and Statistical Manual of Mental Disorders (DSM; American Psychiatric Association [APA], 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flowers et al (2020) andAfrahi et al (2021) were followed while reporting content of research question 3.Small number of studies (n=8) from the reviewed literature has focused on antecedents to spousal support for working population and they are all either personal or work-family related variables. Gender differences was significantly affecting the spousal support offered to working population, it means the support offered relies on the gender of the spouse offering the support.…”
mentioning
confidence: 99%